2014
DOI: 10.1002/ejlt.201300254
|View full text |Cite
|
Sign up to set email alerts
|

Consumer discrimination of Chemlali and Arbequina olive oil cultivars according to their cultivar, geographical origin, and processing system

Abstract: The chemical composition and consumer preferences according to consumer characteristics of virgin olive oils (VOOs) from "Chemlali" and "Arbequina" cultivars were studied in relation to processing system and geographical origin. Statistical analyses revealed significant differences (p < 0.05) among cultivars in % free acidity, K 270 , and OSI values, pigments, and antioxidant content and in some FAME content. Significant differences were also found according to the processing system in terms of some quality in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
9
1
Order By: Relevance
“…In the present study, Sinolea system recorded the lowest free acidity; and the 2-phases system, the highest one exceeding, together with the press system, the limit of 0.8% established by the IOC regulation for extra virgin olive oil [39]. These results are in disagreement with many previous studies that showed a highest free acidity in the press system and a lowest one in the centrifugation systems [36,42,43]. The high level of free acidity observed in the present study in the 2-phases system is probably related to strong infection with the olive fruit fly (Bactrocera olea) in both regions where the 2-phases is present: Chadra in Akkar and Bisri in Jezzine.…”
Section: Factors/statisticscontrasting
confidence: 97%
See 2 more Smart Citations
“…In the present study, Sinolea system recorded the lowest free acidity; and the 2-phases system, the highest one exceeding, together with the press system, the limit of 0.8% established by the IOC regulation for extra virgin olive oil [39]. These results are in disagreement with many previous studies that showed a highest free acidity in the press system and a lowest one in the centrifugation systems [36,42,43]. The high level of free acidity observed in the present study in the 2-phases system is probably related to strong infection with the olive fruit fly (Bactrocera olea) in both regions where the 2-phases is present: Chadra in Akkar and Bisri in Jezzine.…”
Section: Factors/statisticscontrasting
confidence: 97%
“…As per the processing system, the effect was significant on free acidity and K270 ( Table 5). These results are in partial agreement with those obtained by Ben Hassine et al [36], who indicated that the free acidity, the peroxide value, the K232 and the K270 are significantly affected by the processing system. Conversely, Salvador et al [41] demonstrated that while oxidative stability and antioxidant content differed significantly between processing systems; free acidity, peroxide value, K232 and K270 didn't show significant differences.…”
Section: Factors/statisticssupporting
confidence: 92%
See 1 more Smart Citation
“…19 didn t find any difference in the free acidity and in the PV on Chemlali olive oils obtained from olives cultivated on soils irrigated with different quality waters. Other authors 20 found differences comparing Chemlali olive oils belonging to different geographical sites in Tunisia. To evaluate the oxidation level of oil samples the parameters K 232 and K 270 have been used.…”
Section: Quality Parametersmentioning
confidence: 89%
“…The concentration and antioxidant activity of phenolic compounds in VOO is significantly affected by numerous factors such as cultivar, fruit maturity stage (harvesting time) and harvest methods, fruit freshness before extraction, environmental factors (geographical origin, climatic conditions, location, soil, irrigation systems, water stress etc.) extraction process and storage conditions (Alowaiesh et al, 2018;Ben Hasine et al, 2013;Borges et al, 2017;Kiralan et al, 2012;Kiritsakis et al, 2010;Peres et al, 2016;Rodrigues et al, 2019). The ripening stage of olives has a high impact on the oil's yield, quality, stability and sensory characteristics.…”
Section: Factors Affecting the Functional Phenolic Compounds In Olive Oilmentioning
confidence: 99%